Prototype Pemblokir Gambar Pornografi Menggunakan Algoritma Viola and Jones - Muhammad Fikri Hidayattullah; Miftakhul Huda (Jurnal Informatika: Jurnal Pengembangan IT, 2019)
The spread of pornographic content extends very quickly through internet media. Various types of porn sites increase dramatically every day. Various prevention efforts to overcome the spread of pornographic content have been carried out. Starting from URL blocking, text filtering to be more specific directly to pornographic images through skin detection. However, all of these methods have various weaknesses. An effective step to reduce the spread of pornographic images is to block the breast area that is characteristic of the pornographic images. In this study a breast area blocking prototype was developed on pornographic images using the Viola and Jones algorithm.. From the test results obtained a precision value of 82.61%, 77.55% recall and accuracy of 78.26%.